KECERDASAN EMOSIONAL SEBAGAI PEMODERASI PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI, TIME PRESSURE, LOCUS OF CONTROL TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Sesty Ferica Purba; Muhammad Nuryatno (Jurnal Akuntansi Trisakti, 2019)
This objectives of the research to empirically analyze independence, time pressure, and locus of control on the detection of fraud with emotional intelligence as a moderating variable. The population in this study is the auditor who works at the Public Accountant Office in DKI Jakarta in a cluster sampling method, namely the auditor with a minimum of 2 years working experience. Respondents obtained for this study were 154 respondents. Data were analyzed using Moderated Regression.The results showed that skepticism, independence, locus of control had a positive effect on the ability of auditors to detect fraud. However, time pressure does not affect the ability of auditors to detect fraud. This study also shows that emotional intelligence strengthens the effect of independence on the auditor's ability to detect fraud and this research shows that emotional intelligence does not strengthen the influence of professional skepticism, time pressure and locus of control on the auditor's ability to detect fraud.